Toxicological effects of TiO2 nanoparticles in two freshwater species: carassius auratus and corbicula fluminea - Lourenço, Joana Filipa Cardoso (2015)
Titanium dioxide (TiO2) nanoparticles (NPs) have a widespread use, from industrial applications to consumer products. The increasing use of nanomaterials can lead to significant releases of NPs into environment and the aquatic system is commonly the ultimate recipient for NPs. However, the impact and potential detrimental effects of NPs to aquatic biota remains unclear. In this context, the aim of the present work is to evaluate the toxicity of the TiO2 NPs exposure in two freshwater species (Carassius auratus and Corbicula fluminae). Organisms were exposed to suspensions of TiO2 NPs (±21 nm) within a range of concentrations from 0.01 to 800 mg TiO2/L and sampled for enzymatic and histological analysis after periods of 7, 14 and 21 days. Lipid peroxidation, superoxide dismutase, catalase and glutathione-s-transferase activity were determined in order to evaluate the response to oxidative stress. Tissues from target organs were analyzed by optical and electron microscopy and x-ray elemental analyses allowed detecting the presence of TiO2. The exposure to TiO2 NPs in aquatic suspensions was not lethal for C. auratus, but significant mortality rates were found for C. fluminea. Results show that TiO2 NPs causes toxicity involving oxidative stress, increasing lipid peroxidation and inducing significant variations of the antioxidant activity in the exposed organisms compared to controls and over exposure time. Histological pathologies were observed in C. auratus gills, liver and intestine and in C. fluminea digestive gland. NPs in suspension are ingested by organisms, resulting in the accumulation of TiO2 NPs agglomerates inside C. auratus intestinal lumen. Cellular internalization of TiO2 NPs was confirmed in cells from fish gills. The results suggest that, a potential risk to the aquatic biota exist related to the TiO2 NPs release to the aquatic environment. The environmental impact of the NPs is a matter of concern and despite an increase of studies of nanosized-TiO2 effects, the precise mechanisms of toxicity of this and other metal NPs remain unclear.